ANALISIS PENGARUH TEKNOLOGI AI PADA PROSES PEMBELAJARAN MUSIK - Agung Trian Daffa; Riyan Hidayatullah (Jurnal Manajemen Pendidikan, 2026)
While AI offers many advantages, its implementation in music learning is not without challenges. The emotional and aesthetic interactions typically present in traditional music learning can be diminished if overly reliant on technology. Furthermore, there are concerns that the use of AI could diminish the role of teachers or lead to dependence on digital devices. Therefore, a comprehensive analysis is needed to determine how AI can be used in a balanced way without diminishing the essence of music learning itself. This study aims to analyze the influence of artificial intelligence (AI) technology on the music learning process using a literature review approach. The main issue studied is how AI changes the way students understand theory, practice, and creativity in music. Through a review of various scientific sources such as journals, books, and recent research reports, this study highlights the role of AI in enhancing learning personalization, providing automated feedback, and expanding access to digital music materials. The literature review method allows researchers to identify patterns, benefits, and challenges of using AI in music education. The results show that AI technology can enrich the learning experience, strengthen musical analysis skills, and assist teachers in designing more adaptive learning, but still requires human guidance to maintain pedagogical quality and students' creative aspects.